2022
DOI: 10.1187/cbe.21-05-0125
|View full text |Cite
|
Sign up to set email alerts
|

“How Do We Do This at a Distance?!” A Descriptive Study of Remote Undergraduate Research Programs during COVID-19

Abstract: This study describes the design and implementation of remote Summer undergraduate research programs during the COVID-19 pandemic, including program strengths and recommendations for improvement from the perspectives of undergraduate researchers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Research on 23 remote 2020 summer research programs identified technology issues as one of the challenges that limited participants’ experiences. Some students did not have suitable Internet connections, access to computers with sufficient computing capacity or credentialing to allow access to essential software [ 13 ]. One can imagine students struggling with the time pressures it takes to troubleshoot Internet issues or set up new services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on 23 remote 2020 summer research programs identified technology issues as one of the challenges that limited participants’ experiences. Some students did not have suitable Internet connections, access to computers with sufficient computing capacity or credentialing to allow access to essential software [ 13 ]. One can imagine students struggling with the time pressures it takes to troubleshoot Internet issues or set up new services.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are examining how these changes have impacted student well-being [ 2 , 3 , 4 , 5 ], learning and academic engagement [ 6 , 7 , 8 ], relationships with peers [ 9 ] and longer-term outcomes, such as retention and delayed graduation [ 10 , 11 ]. Few studies have examined how COVID-19 has impacted undergraduate research training [ 12 , 13 , 14 ], and few have focused on initial experiences during the early months of the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also amenable to in-person, hybrid, and remote models of instruction, with internet access being the only requirement for implementation of the project. In light of the impact of the COVID-19 pandemic on both classroom instruction and independent research opportunities for students [ 30 ], this flexibility is beneficial for undergraduate coursework in several STEM disciplines, as well as for summer and academic-year research programs that have yet to return to full capacity due to ongoing concerns over the pandemic and that may therefore wish to expand this approach into more extensive independent research projects for students.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, many undergraduates, including those at the University of Washington, spent nearly a full year learning remotely, and undergraduate researchers lost their on-campus work–study research positions. , We set out to re-employ the work–study undergraduate researchers at our Institute by offering a virtual research opportunity, which has been reported to be beneficial and valuable for students in other undergraduate research programs. , However, we needed a different approach than our previous apprenticeship model, as the frequent 1:1 contact central to that model was impractical to implement remotely and too few mentors were free to individually work with each undergraduate at our Institute. Previous cohort-based research courses in computational protein design, in which multiple students are taught by a smaller number of mentors, enabled them to accommodate greater numbers of students and have shown significant success in increasing students’ enthusiasm for biochemistry and computational biology. We adopted this cohort-based model and curated a completely remote computational curriculum that allowed students to take ownership of their portion of a team research project while learning from each other.…”
Section: Introductionmentioning
confidence: 99%